Analisis Faktor Penyebab Fenomena Ngopi Dalam Budaya Work From Cafe: Studi Perilaku Konsumen - Vidya Nindhita; Afif Arifin (Journal of Social, Culture, and Language, 2024)
The phenomenon of coffee and work from café started to spread after the COVID-19 pandemic. The younger generation in general prefers to spend a lot of time doing activities in a café for both work and social reasons. Looking at the various reasons used to always carry out activities in coffee shops and cafes is an interesting study to add to the repertoire of knowledge about consumer behavior. This study aims to answer the question of how consumer behavior underlies the decision of the younger generation to hang out at a cafe, especially a coffee shop? The preparation of scientific articles is carried out using the literature review method. The journal articles searched were limited to research from 2019 to 2024.  The keywords used were "consumer behavior", "lifestyle", "cafe", and "coffee shop". Journal articles were selected according to the following criteria: (1) Contains the results of research on consumer behavior; (2) The research was conducted with subjects from generation Y and generation Z; (3) The research was conducted in the context of activities in cafes as a place of choice. In this review, there are 8 studies that fit the theme and criteria. Some of the things supporting consumer behavior that underlie the decision of the younger generation to hang out at a cafe, especially coffee shops, are divided into self-related, social, task/work, and lifestyle. The phenomenon of coffee is becoming increasingly embedded with the work from café culture that is promoted as an alternative to working outside the office. Keywords: Coffee, Consumer Behaviour, Work From Café